Well-Being as a Cognitive Load Reducing Agent: A Review of the Literature - Hawthorne, Benjamin. S.; Vella-Brodrick, Dianne. A.; Hattie, John (Frontiers in Education, 2019)
Cognitive Load Theory is an evolutionary based theory of learning centered upon the cognitive architecture of the brain, which outlines a series of empirically based instructional effects that ensure efficient and effective learning. While the research upon which Cognitive Load Theory is based has generally aimed at controlling the impacts of the surrounding environment, the impact of individual psycho-social factors such as a student’s level of wellbeing have not, as yet, been fully explored. This review was conducted using the Scopus database focusing on the Cognitive Load Theory Instructional Effects literature. The review proposes that wellbeing may act as a cognitive load reducing agent for students and offers evidence from the broader literature on mechanisms through which wellbeing reduces the cognitive load placed upon a student’s working memory. The proposed mechanisms of reducing extraneous load and increasing germane load are proposed through; the presence of positive emotions, the absence of painful emotions, high levels of academic buoyancy and cognitive regulation.